STUDENTS’ PERCEPTION OF PROBLEM-BASED LEARNING IN ELEMENTARY SCHOOL TEACHER EDUCATION - Erif Ahdhianto; Muh. Arafik; M. Anas Thohir; Siti Mas’ula (Widyagogik, 2021)
The recent rise in the use of problem-based learning (PBL) has given rise to serious debates over its introduction. PBL critics question whether emphasizing practice makes teachers less inclined to impart educational content that is responsive to students’ ideas, preferring instead to employ a technocratic approach. This research seeks to expand on the basis of its effectiveness as a means of engaging students in learning and incorporating literature on the Problem- based web learning method. The hypotheses, therefore, address the effect of the PBL method on collaborative learning.  As a means of data collection, a questionnaire was formulated and given to 464 Elementary School Teacher Education Students who approached with a problem-solving methodology. To study the application of PBL, a quantitative research technique was used to figure out the findings of the investigation. SPSS and Structural Equation Method (SEM-AMOS) were used to arrive at the results. Learners’ engagement was raised as a result of implementing learning methods like active learning, iterative learning, and authentic learning. The results indicate that students are encouraged to participate in Problem Base Web Learning, which increases engagement by allowing students to share and discuss their findings. Therefore, PBL is essential such that students are encouraged to employ this approach in their academic endeavours. Further, universities also similarly urge them to do so.